Impact of Corporate Governance Practices on Firm's Cash Holdings in an Emerging Market: A Panel Data Analysis - Kengatharan, L. (International Journal of Accounting and Financial Reporting, 2017)
The aim of the study was to examine the impact of corporate governance practices on firm's cash holdings of listed manufacturing companies in Sri Lanka, using panel data extracted from the financial statements of the companies listed on Colombo Stock Exchange. Corporate governance practices of Sri Lankan listed manufacturing companies were measured by board independence, board size, CEO duality, audit committee meetings and audit committee members, cash holdings were measured by percentage of cash and cash equivalents on total assets and also leverage and firm size were considered as control variables. Data were collected from 26 listed manufacturing companies over a five years period of 2011-2015. Pooled Ordinary Least Square, Fixed Effect and Random Effect models were performed using STATA to explore the best model for the impact of corporate governance practices on firm's cash holdings. Results of the study revealed that fixed effect model was the best model with the evidence of Hausman specification test. According to the fixed effect model, CEO-duality and leverage had significant negative impact on cash holdings while audit committee meetings and firm size had positive impact on cash holdings of the listed manufacturing companies in Sri Lanka. Board independence, board size and audit committee members did not show any significant impact on cash holdings. Findings of the study may be useful to practitioners to identify the effects of corporate governance practices on firm's cash holdings.
Keywords: corporate governance; leverage; cash holdings